The application of computational techniques to the design of thermal ice protection systems - Leah, C. W. (Cranfield University, 1990)
A bibliography citing 1350 references related to all aspects of aircraft icing is presented. An ice adhesion database has been compiled, and a survey of ice adhesion test rig designs is presented. An ice shear adhesion test rig is designed, manufactured and operated. The results are added to and compared with those in the database. The adhesion of ice accreted on metal and non-metallic composite aircraft propeller blades in flight is assessed. A one-dimensional thermodynamic study of ice accreted on a non-metallic composite propeller blade with ’built-in1 electrothermal de-icing system is effected and compared with a solid metal blade. A two-dimensional aerofoil icing prediction program is modified and executed in series with additionally created software to predict icing on aircraft engine air intake duct lips in flight. Hence a new de-icing system design method is developed to replace and improve upon an existing one. Validation of the new design method is initiated and a programme for its completion is presented. Icing predictions produced using the new method correlate well with expected values derived by several methods. The new design method is incorporated in the sponsoring companies business with an appropriate computer hardware/software system and employed, in parallel with the ’old’ approach (till validation completion), on commercial projects. Market response indicates a definite preference for the new design method. The ’non-technical’ and other related practical topics of implementing the new de-icing system design method, including specification and installation of computer hardware and software are discussed. Marketing, financial and other commercially oriented subjects are addressed in justifying the research and the implications of introducing the new design method into the commercial business of the sponsoring organisation are considered. This research programme forms a part of a large, long term icing research commitment. Continued research subjects and investigative routes including the integration of ice adhesion mechanical characteristics into the de-icing system design method are discussed together with their relationship to this and the overall icing research plan.